The diffusion of financial innovations: an examination of the adoption of small business credit scoring by large banking organizations - Jalal Akhavein; W. Scott Frame; Lawrence J. White (Federal Reserve Bank of Atlanta, 2001)
Financial innovation has been described as the "life blood of efficient and responsive capital markets." Yet, there have been few quantitative investigations of financial innovation and the diffusion of these new technologies. Of the latter, there have been only three prior quantitative studies, and all three used the same data set on automated teller machines! ; This paper makes a significant contribution to the financial innovation literature by examining the diffusion of a recent important innovation of the 1990s: banks' use of credit scoring for small business lending. The authors examine the responses of 95 large banking organizations to a survey that asked whether they had adopted credit scoring for small business lending as of June 1997 (56 had done so) and, if they had adopted it, when they had done so. The authors estimate hazard and tobit models to explain the diffusion pattern of small business credit scoring models. Explanatory variables include several market, firm, and managerial factors of the banking organizations under study. ; The hazard model indicates that larger banking organizations introduced innovation earlier, as did those located in the New York Federal Reserve district; both results are consistent with expectations. The tobit model confirms these results and also finds that organizations with fewer separately chartered banks but more branches introduced innovation earlier, which is consistent with theories stressing the importance of bank organizational form on lending style. Though the managerial variables signs are consistent with our expectations, none yields significant results.
Keywords: 330; Credit scoring systems; Financial modernization; Commercial loans; Bank loans